PERANCANGAN TRAINER ESP32 INTERNET OF THINGS PADA MATA PELAJARAN PEMROGRAMAN DAN APLIKASI MIKROKONTROLER DI SMK NEGERI 7 BEKASI - FADLY NENDRA (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2026)
The ESP32 Internet of Things Trainer is designed as a solution to reduce learning problems in the Microcontroller Programming and Applications Subject in class XI Audio Video Engineering at SMK Negeri 7 Bekasi. The main objective of this study is to assess the feasibility level of the ESP32 Internet of Things media trainer product based on assessments from material experts, media experts, and instructional design experts and to determine the effectiveness of the product on students. The development method used is the Research & Development (R&D) development method with the ADDIE development model which is implemented in five stages, namely Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). The final product produced is the ESP32 Internet of Things media trainer which has been tested for feasibility by material experts, media experts, instructional design experts, and tested directly with class XI Audio Video Engineering students at SMK Negeri 7 Bekasi. In this study, the percentage of feasibility obtained by material experts was 91.7%, media experts obtained a percentage of 98.2%, and instructional design experts obtained a percentage of 80.9%. In the individual trial (One to One) conducted by 3 students, the percentage obtained was 94.6%, while for the small group trial (Small Group) conducted by 10 students, the percentage obtained was 92%. Overall, it can be concluded that the ESP32 Internet of Things media trainer is very suitable for use in learning activities.